L’arte di vivere ne Il professore di Viggiù di Aldo Nove. Uno studio sulla vita umana sulla base di un’intervista mai avvenuta - Kobylska, Dominika (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The analysis presented in this article concerns one of the newest philosophical novelsof Aldo Nove, entitled Il professore di Viggiù (2018). In the book the author presents an inventedinterview with mysterious person, by which he transmits reflections on human life in the modernworld. The text evokes the existential issues concerning the increasingly precarious conditionsin which people live torn between doubts about the reality of their own being. The aim ofthe research is to emphasize the motifs which can be seen in the work of the Italian writer andto answer the questions related to his way of showing the consumer society